Status of Immunotherapy Acceptance in Chinese Patients With Multiple Sclerosis: Analysis of Multiple Sclerosis Patient Survival Report 2018 - Zhou, Ran; Zeng, Qiuming; Yang, Huan; Xu, Yan; Tan, Guojun; Liu, Hongbo; Wang, Lihua; Zhou, Hongyu; Zhang, Meini; Feng, Jinzhou; Jin, Tao; Zhang, Xinghu; et al. (Frontiers in Neurology, 2021)
Objective: The prevalence of multiple sclerosis (MS) in China is low, although it has been increasing recently. Owing to the paucity of data on immunotherapy acceptance in the Chinese population, we conducted this study to analyze factors affecting the acceptance of immunotherapy and selection of disease-modifying therapies (DMTs) based on personal and clinical data of patients with MS. Methods: In this study, data were obtained from the Multiple Sclerosis Patient Survival Report 2018, which was the first national survey of patients with MS in China. There were 1212 patients with MS from 31 provinces who were treated at 49 Chinese hospitals over a 4-month period from May 2018 to August 2018, and the patients were asked to complete online questionnaires to assess their understanding of the disease. Results: In general, highly educated patients with frequent relapses were more willing to receive treatment regardless of DMTs or other immunotherapy, and patients with more understanding of the disease opted to be treated. Younger patient population, patients with severe disease course, and those with more symptoms were likely to choose the treatment. Moreover, a higher proportion of women chose to be treated with DMTs than with other immunotherapies. Conclusions: Education status and patient awareness of the disease impact the treatment acceptance in Chinese patients with MS. Therefore, we call for improving the awareness of MS disease and social security to help patients to improve their quality of life.